THE EFL PRE-SERVICE TEACHERS' PERSPECTIVES AND EXPECTATIONS TOWARDS MICROTEACHING: A CASE STUDY AT AN ENGLISH DEPARTMENT, IN A PUBLIC UNIVERSITY - Aslamia, RTS. Suaibatul (Langue (Journal of Language and Education), 2024)
Teaching practice in real educational environment is an obligation course for student teacher of teacher training and education faculty. This course is believed to be very significant as authentic experience to create professional educator by training. However, student teacher has to follow microteaching program before teaching practice at school as a set of teaching practice preparation (Ismail, 2011) which provided by university to be qualified pre-service teacher. This study was conducted as qualitative research with a case study approach. It was commonly used to understand peoples' experiences and to express their perspectives (Creswell, 1994). Furthermore, this study used triangulation data sources, consisting of: (1) demographic questionnaire, (2) face-to-face interview, and (3) observation that consisted of video as visual data, to conduct high quality research with an excellent way (Christensen & Johnson, 2008). The first, microteaching gave knowledge about teaching technical steps. This finding was relevant with another research that microteaching provided and developed knowledge of methodological teaching skill (Sen, 2009). However, findings in this study provided very specific technical teaching skill that gained by EFL pre-service teachers during the implementation of microteaching, such as a teacher should design lesson plan before coming to class, besides on lesson plan they had to pay attention with several points like material that would be taught and then decided appropriate steps in teaching that material to student on accurate time allocation. Second, the advantages of microteaching were teaching practice which gave opportunities to smoothness pre-service teachers' teaching skill (Ismail, 2011) which been the most important point of microteaching itself. However, not only well preparation that needed by EFL pre-service teachers to be an educator, but also well teaching was also significant.